Organisation et activites du programme du CIAT sur le haricot visant a appuyer les programmes nationaux de recherche en Afrique - Kirkby, Roger A. (International Center for Tropical Agriculture, 1987)
CIATS`s bean research activities in Africa aim at meeting the needs of bean-producing areas in East, Central, and southern Africa. Efforts of national research programs are effectively supported in areas such as breeding, improved cultural practices and cropping systems, training, on-farm evaluation, seminars and workshops, and bean documentation services. (CIAT)